No significant change in MRI abnormalities or back pain prevalence in the thoraco-lumbar spine of young elite skiers over a 2-year follow-up - Witwit, W. A.; Hebelka, H.; Swärd, A. A.; Abrahamson, J.; Todd, C.; Baranto, A. (Open Access Journal of Sports Medicine, 2022)
Background Young athletes are at increasing risk for spinal column injuries due to overloading the spine with excessive sports activities, with potential development of complications later in life.